Hippocampal Functioning and Verbal Associative Memory in Adolescents with Congenital Hypothyroidism - Wheeler, Sarah M.; McLelland, Victoria C.; Sheard, Erin; McAndrews, Mary Pat; Rovet, Joanne F. (Frontiers in Endocrinology, 2015)
Thyroid hormone (TH) is essential for normal development of the hippocampus, which is critical for memory and particularly for learning and recalling associations between visual and verbal stimuli. Adolescents with congenital hypothyroidism (CH), who lack TH in late gestation and early life, demonstrate weak verbal recall abilities, reduced hippocampal volumes, and abnormal hippocampal functioning for visually associated material. However, it is not known if their hippocampus functions abnormally when remembering verbal associations. Our objective was to assess hippocampal functioning in CH using functional magnetic resonance imaging (fMRI). Fourteen adolescents with CH and 14 typically developing controls (TDC) were studied. Participants studied pairs of words and then, during fMRI acquisition, made two types of recognition decisions: in one they judged whether the pairs were the same as when seen originally and in the other, whether individual words were seen before regardless of pairing. Hippocampal activation was greater for pairs than items in both groups, but this difference was only significant in TDC. When we directly compared the groups, the right anterior hippocampus was the primary region in which the TDC and CH groups differed for this pair memory effect. Results signify that adolescents with CH show abnormal hippocampal functioning during verbal memory processing.